Financing Africa - Waris, Attiya (Langaa RPCIG, 2019)
Financing Africa's development requires ingenuity, discipline, and an understanding of fiscal systems - the entirety of government revenues and expenditures, including taxation and debt. This book makes fascinating what might seem at first glance complex. It describes diverse approaches that have been adjusted to local circumstances across the continent and reflects on the push to unite and harmonise toward African union. Africa is rich, yet resources are lost through loopholes in fiscal systems. Financial resources come from the people, are not unlimited, and do not come easily or without cost. Africans must therefore cherish these resources and use them in nation-building and national and regional development. Efficient, effective, transparent and accountable fiscal systems that are fair and just will go a long way toward financing Africa's development. Using examples from all of Africa's 54 countries, the book makes fiscal matters real and understandable for people, no matter their field. It demonstrates the importance of fiscal law and policy for development and the impact it has on individuals, communities, nations, regional groupings, and the continent.